ACTIVE ELEMENTS : Gain distribution in the volume of a solid-state active element of a diode-pumped high-power laser. (28th July 2017) - Gushchik, T I; Drakin, A E; D'yachkov, N V; Romanov, V V
Abstract: We propose a technique for calculating the spatial gain profile in the volume of a solid active element of a high-energy laser pumped by laser diode arrays, which takes into account the properties of the radiation pattern of semiconductor lasers. This technique is employed to calculate the profile of the gain in a neodymium glass active element. By the example of a rod of rectangular section 4.5 by 4.5 by 25 cm we show that, by varying the pump system parameters, it is possible to define the profile of the gain: for instance, a profile uniform over the cross section (with its nonuniformity under 2.5%), with a peak at the centre or in peripheral regions, with a specific energy deposition of ∼1 J cm -3 .